2007
DOI: 10.3324/haematol.10874
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of 134 Brazilians with acute promyelocytic leukemia who received ATRA and anthracyclines

Abstract: We report an increased incidence of high relapse risk features in 157 APL Brazilian patients. Out of 134 patients treated with ATRA and anthracyclines, only 91 (67.9%) achieved remission because 43 (32%) died during induction. The death rate during consolidation was 10.5%. Bleeding complications were the most frequent cause of failure (21.6%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
71
1
8

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 6 publications
11
71
1
8
Order By: Relevance
“…This is similar to what was reported from Brazil, 22 but considerably higher compared with recent European and North American clinical trials. 3,4,[8][9][10] The main reason for the higher ED in the Swedish Registry compared with clinical trials is probably the inclusion of patients with very early deaths, as well as of patients who were not fit or too old for inclusion in clinical trials.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is similar to what was reported from Brazil, 22 but considerably higher compared with recent European and North American clinical trials. 3,4,[8][9][10] The main reason for the higher ED in the Swedish Registry compared with clinical trials is probably the inclusion of patients with very early deaths, as well as of patients who were not fit or too old for inclusion in clinical trials.…”
Section: Discussionsupporting
confidence: 78%
“…ED in this study was defined as death within 30 days from diagnosis. Although some reports define ED as deaths within 10 or 14 days, 12,22 other studies show that typical APL-dependent deaths, such as hemorrhagic deaths due to coagulopathy and death from differentiation syndrome, can occur during the third and fourth week after start of treatment. 11 Still, only two of the 30 deaths occurred more than 14 days after diagnosis, and the ED rate within day 14 was still as high as 27%.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of blood counts at the time of diagnosis for individual types of leukemia roughly corresponded to findings in previously published studies [9,11,[17][18][19][20][21][22]. Nevertheless, it is important to note that even though the total leukocyte (LEU) counts were highest in CML cases (median 93 3 10 9 /l), these values only represent 40-50% of the median LEU counts in the analyses published two to four decades ago [9,20].…”
supporting
confidence: 86%
“…Despite the incorporation of ATRA, hemorrhage remains the major cause of early death (4.5 %); other causes of early death include infection (1.9 %) and differentiation syndrome (1.2 %) [20] (Table 1). Moreover, population-based studies have shown that the early death rate during induction chemotherapy remains extremely high (30 %), and the most common cause of death is associated with hemorrhage [24][25][26] (Table 1). Thus, development of a novel treatment strategy to alleviate coagulopathy in APL patients is urgently required.…”
Section: Introductionmentioning
confidence: 99%